Ðš Ñ‚ÐµÐ¾Ñ€Ð¸Ð¸ Ð´Ð¸Ð°Ð³Ñ€Ð°Ð¼Ð¼ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð½Ñ‹Ñ… Ñ€Ð°ÑÑ‚Ð²Ð¾Ñ€Ð¾Ð² - Osetsky, Aleksandr I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
The paper considers the advantages of cluster crystallization model when describing phase transitions in cryoprotective solutions. The principles of plotting the diagrams of state are described, with emphasis on the fields of existing cluster phase. Basing on these diagrams the experimentally observed heat and volume effects are analyzed, which accompany the crystallization and melting of cryoprotective solutions. Herewith a special attention is paid to the distinguishing of phase curves, corresponding to cooling and following heating of the solutions and the definition of superposed diagrams of state was made to describe the processes caused by appearing differences. Model of cluster crystallization was used to determine the balanced structure state of frozen cryoprotective solutions and possible processes directed to their achieving. Probl Cryobiol Cryomed 2014; 24(2):102-117.